1979
DOI: 10.1056/nejm197911293012203
|View full text |Cite
|
Sign up to set email alerts
|

Increased Insulin Sensitivity and Insulin Binding to Monocytes after Physical Training

Abstract: We studied the effect of physical training on in vivo tissue sensitivity to insulin and insulin binding to monocytes in six previously untrained healthy adults. Physical training (one hour of cycle-ergometer exercise four times per week for six weeks) failed to alter body weight but resulted in a 20 per cent increase (P less than 0.02) in maximal aerobic power (VO2 max) and a 30 per cent increase (P less than 0.01) in insulin-mediated glucose uptake (determined by the insulin clamp technique). The increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
72
1
3

Year Published

1982
1982
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(85 citation statements)
references
References 28 publications
9
72
1
3
Order By: Relevance
“…Insulin secretion is inhibited by increased sympathetic nervous system activity via a-adrenergic receptors, and plasma insulin concentrations decline to low levels (6,(23)(24)(25). This results in increased lipolysis in adipose tissue and increased hepatic glucose production (26,27).…”
Section: Ls Hortonmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin secretion is inhibited by increased sympathetic nervous system activity via a-adrenergic receptors, and plasma insulin concentrations decline to low levels (6,(23)(24)(25). This results in increased lipolysis in adipose tissue and increased hepatic glucose production (26,27).…”
Section: Ls Hortonmentioning
confidence: 99%
“…The low insulin concentration during exercise also promotes lipolysis, making FFAs available for oxidation by exercising muscle and glycerol available to the liver for gluconeogenesis. In the insulin-treated diabetic patients, plasma insulin concentrations do not decrease during exercise and may even increase substantially if exercise is undertaken within an hour or so of an insulin injection (6,(61)(62)(63). This effect is due to increased absorption of insulin from the subcutaneous tissue, particularly if the injection site is in an exercising part of the body (64).…”
Section: Metabolic Fuel Homeostasis During Exercise In Type I Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown positive health benefits with low-intensity exercise (Dunstan et al 1997;Poirier et al 2002;Soman et al 1979;Tessier et al 2000). Greater intensities of exercise tend to yield even greater benefits (1996), particularly changes in hemoglobin HbA 1c levels and aerobic capacity (Mourier et al 1997).…”
mentioning
confidence: 99%
“…3 Current management is controversial and not adequate. In obese patients, loss of weight, 2,15 as well as exercise, 16 helps in reducing the insulin resistance. Gonadotropin suppression by the combined pills has been reported by many to help in reduction of ovarian hyperandrogenism.…”
Section: Discussionmentioning
confidence: 99%